2010
DOI: 10.4028/www.scientific.net/amr.152-153.136
|View full text |Cite
|
Sign up to set email alerts
|

Study on Photodynamic Therapy for HL60 Cells Inactivation by Visible Light-Induced Fe-Doped Nano-TiO<sub>2</sub> under Magnetic Field

Abstract: Fe-doped TiO2 was prepared by a homogenous precipitation method and characterized by XRD, UV-Vis DRS. The structure and the optical properties of nano-TiO2 with different Fe doping content were studied, as well as the effect and the possible mechanics of different intensity of TiO2 particles, Fe-doped nano-TiO2 particles on the activity of HL60 leukemic cells. The influence on the activity of cells exposures in light compared with un-exposure also be analysed. As the photo sensitizers, TiO2 and Fe-doped TiO2 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…An increased uptake of cytotoxic agents and magneto-cell lysis producing mechanical tumor ablation is speculated. For instance, the effect of TiO 2 and Fe-doped TiO 2 MNP on the activity of HL60 leukemic cells was studied by observing the influence on the activity of cells exposed to light compared to un-exposure [70]. It was observed that the PS (TiO 2 ) completely eliminated tumor cells using illumination under an applied magnetic field..…”
Section: Magnetic Drug and Gene Targeting: Magnetoporationmentioning
confidence: 99%
“…An increased uptake of cytotoxic agents and magneto-cell lysis producing mechanical tumor ablation is speculated. For instance, the effect of TiO 2 and Fe-doped TiO 2 MNP on the activity of HL60 leukemic cells was studied by observing the influence on the activity of cells exposed to light compared to un-exposure [70]. It was observed that the PS (TiO 2 ) completely eliminated tumor cells using illumination under an applied magnetic field..…”
Section: Magnetic Drug and Gene Targeting: Magnetoporationmentioning
confidence: 99%